REGIONAL DEVELOPMENT IN ROMANIA. A BRIEF STATISTICS ON SOCIO-ECONOMIC DIFFERENCES-A MULTI-CRITERIAL APPROACH - Agatha POPESCU; Toma Adrian DINU; Elena STOIAN; Valentin ŞERBAN; Mirela STANCIU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper analyzed the development in the NUTS 2 of Romania in the year 2022 using a large spectrum of socio-economic criteria including 32 indicators, destined especially to emphasize the contribution of agriculture to the social and economic growth. The data were picked up from the National Institute of Statistics and Eurostat database. The processing methodology included: structural indices, comparisons among regions, rank-order method to establish the hierarchy based on the region performance. The results reflected the population polarization in North East, South Muntenia, North West and South East and also in Bucharest-Ilfov. Rural population and the one dealing with agriculture is concentrated in North East, South Muntenia, North West and South East. But, the occupied persons in the economy are in Bucharest Ilfov, North West, Center and West. The largest cultivated area and the highest value of agricultural production are in South Muntenia, South East, South West Oltenia, West and North East. The highest value of agricultural production per inhabitant is in South Muntenia, South East, South West Oltenia, West and North East. Labor productivity is higher in Bucharest Ilfov, West, North West and Center. The highest average monthly income, expenditures and savings rate per household is in Bucharest Ilfov, North West, Center and West. Income from agriculture per household is higher in North East, West, South East and North West, while per person is higher in Bucharest Ilfov, South Muntenia, North West and South East. GDP has the highest level is in Bucharest Ilfov, West, Centre, North West, while in North East, South Muntenia, South West Oltenia and South East is lower. In 2022, Romania achieved Euro 26,700 per capita (PPS) (75% of the EU average), coming on the 22 position among the other EU countries. Based on all these criteria, the final hierarchy of the NUTS 2 regions in Romania in 2022 was in the decreasing order: South Muntenia, South East, North West, West, Center, Bucharest Ilfov, South West Oltenia and North East which reflects the existence of discrepancies among regions. Romania has to intensify its efforts to assure a higher rate of economic growth on the principle of equity in the territory and reach a balanced and harmonized economic and social development which, also, have to reduce the gaps compared to the other NUTS 2 regions. For attaining this objective, Romania must to use the EU (TFEU) cohesion funds (2021-2027) to strengthen its economic, social and territorial cohesion and to assure a harmonious and balanced development.